(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study and analysis of biological data using information technology applications and computer technology techniques is known as bioinformatics. Bioinformatics represents biological data in a more effective and efficient way so that non-biologists can interpret it. A species is one of the fundamental components of biological classification and a taxonomic rank in biology.